Strategic Plan for the Development of A Nursing Care Dashboard as A Clinical Decision Support Tool - Devy Feby Febyola Siahaan; Vivianti Fraliana Lesnussa; Ika Chandra Nuryana; Erenda Pratiwi; Rina Ainurrahmah; Ibnu Malik; Rr Tutik Sri Hariyati (GLOBAL HEALTH SCIENCE GROUP, 2026)
The advancement of information technology has driven the transformation of data-based nursing systems through the utilization of nursing care dashboards to support clinical decision-making. This study aimed to analyze the development of a nursing system based on a nursing care dashboard in supporting clinical decision-making at Hospital A Tangerang. This study employed a case study design with an exploratory approach through observation, interviews, and document review. The respondents in this study consisted of 20 participants, including 10 nurse managers and 10 staff nurses working in inpatient units. The data were analyzed using SWOT, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal - External (IE) Matrix, and TOWS. The results showed that the system was in a growth and build position with an IFE score of 2.88 and an EFE score of 3.06. Key strengths include integrated data availability, nursing staff competency, and management commitment, while weaknesses include limited analytical capability, suboptimal system integration, and underutilization of the dashboard in clinical decision-making. Strategic development focuses on optimizing dashboard utilization, enhancing nurses' digital competencies, and strengthening system integration. The development of a nursing dashboard-based system has the potential to improve the quality and timeliness of clinical decision-making and enhance nursing care quality.